Exploring the Interplay of Distance Education, Learning Styles, and Emotional Experiences in High School Students: A Structural Equation Modeling Perspective - Akram Malekzadeh; Parisa Zare; Khatoon Pourmaveddat (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2024)
Background: Distance education is an opportunity to overcome the limitations of face-to-face education and has provided the idea of education for everyone and everywhere. The current study aimed to examine the correlation between distance education and learning styles, incorporating the mediating influence of emotional experiences among high school students.Methods: The research methodology was correlation type. The statistical population comprised all the first-year high school students in Shiraz City during the academic year spanning November 2023 to 2022, with a sample size of 300 individuals selected through convenience sampling. The research tools included Kolb’s Learning Styles Questionnaire, Sekou and Samson’s Distance Space Questionnaire, and Pekrun et al.’s Emotional Experiences Questionnaire. The data analysis involved utilizing Pearson’s correlation coefficient, path analysis, and structural equation modeling through SPSS V26 and Amos V24 software.Results: The results of the present study showed a significant and positive correlation between learning styles and positive emotions. The coefficients indicated a significant correlation between positive emotions with concrete experience (r=0.21, P=0.01), reflective observation (r=-0.25, P=0.01), conceptualization (r=0.18, P=0.02), and concrete experience (r=0.32), (P=0.01). Negative emotions showed a weak correlation with objective experience (r=-0.19, P=0.02) and observation of reflection (r=-0.21, P=0.01), while no significant relationship was found between negative emotions and the abstract conceptualization learning style (r=0.07, P=0.09). There was also a significant correlation between learning styles and distance education. There was a negative correlation between distance education and objective experience (r=-0.18, P=0.02), while there were positive correlations with reflective observation (r=0.35, P=0.01), abstract conceptualization (r=0.42, P=0.01), and another positive correlation with reflective observation (r=0.29, P=0.03).Conclusion: The results showed that positive emotions can help improve distance education even when the student’s learning style is objective experience or active experimentation.